2017
DOI: 10.1016/j.jid.2016.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Increased Levels of the Bullous Pemphigoid BP180 Autoantibody Are Associated with More Severe Dementia in Alzheimer’s Disease

Abstract: Bullous pemphigoid (BP) is a subepidermal blistering skin disease, which has shown a strong association with neurological diseases in epidemiological studies. The BP autoantigens BP180 and BP230 are expressed in the cutaneous basement membrane and the central nervous system. Using BP180 and BP230 ELISA assays and immunoblotting against BP180, we analyzed the IgG reactivity in the sera of 115 patients with Alzheimer's disease (AD) and 40 neurologically healthy controls. BP180 autoantibodies were found in 18% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
76
5
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(98 citation statements)
references
References 41 publications
12
76
5
5
Order By: Relevance
“…Here, we present two cases of elderly patients with BP230‐type BP who had dementia at the onset of BP. A previous study reported that 18% of patients with dementia have IgG autoantibodies to BP180; however, it is unclear whether the production of IgG autoantibodies to BP230 correlates with dementia . Notably, none of our cases showed oedematous erythema that is usually seen in typical BP.…”
contrasting
confidence: 52%
“…Here, we present two cases of elderly patients with BP230‐type BP who had dementia at the onset of BP. A previous study reported that 18% of patients with dementia have IgG autoantibodies to BP180; however, it is unclear whether the production of IgG autoantibodies to BP230 correlates with dementia . Notably, none of our cases showed oedematous erythema that is usually seen in typical BP.…”
contrasting
confidence: 52%
“…A recent study revealed that in a group of patients with Alzheimer’s disease but no bullous pemphigoid, their sera contained much higher level of BP180 autoantibody than neurologically healthy controls. Furthermore, increased levels of the autoantibody were associated with more severe dementia [19]. Thus, it remains unclear whether neurological disease itself could increase the mortality risk, or the increased risk is conferred by functional impairment and decreased autonomy resulting from neurological disease.…”
Section: Discussionmentioning
confidence: 99%
“…Autoantibodies against the immunodominant NC16A domain of BP180 were found in 19% of Alzheimer's disease patients, but only 2% of controls had positive results. The levels of BP180 autoantibodies correlated with the level of cognitive decline 29 . Another factor behind the association between neurological and psychiatric disorders and BP could be the medication used for these diseases.…”
Section: Discussionmentioning
confidence: 92%